Conceptual framework on the relationship between human resource management practices, job satisfaction, and turnover - Mudor, Hamdia (Journal of Economics and Behavioral Studies, 2011)
This paper attempts to propose a conceptual framework consisting of three human resources management (HRM) practice (supervision, job training, and pay practices), job satisfaction, and turnover, and to explain the relationships among these variables. Job satisfaction played an important role to employees’ turnover because it would lead employee resigned when their job satisfaction is low. The results indicate HRM practice a positively and significantly correlated with job satisfaction. On the other hand HRM practice and job satisfaction are negatively and significantly correlated with turnover. However, the results of HRM practice and job satisfaction are strong predictors of turnover.